2008
DOI: 10.1111/j.1742-4658.2008.06785.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver receptor homolog‐1 localization in the nuclear body is regulated by sumoylation and cAMP signaling in rat granulosa cells

Abstract: Liver receptor homolog‐1 (LRH‐1; NR5A2) is an orphan member of the nuclear receptor superfamily, mainly expressed in endoderm‐derived tissues and in the ovary. In ovarian granulosa and luteal cells, LRH‐1 regulates the expression of genes associated with ovarian steroidogenesis. LRH‐1 can be transported to transcriptionally inactive nuclear bodies after conjugation with small ubiquitin‐related modifier (SUMO). In the present study, we investigated the effects of SUMO modification at five lysine residues of LRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Phosphorylation of the serine residues 238 and 243 located within the hinge region of LRH-1 via phorbol 12-myristate 13-acetate (PMA), was found to be important for LRH-1 transactivation [107]. Sumoylation of LRH-1 also occurs in the hinge region, allowing for additional control of its activity via regulation of its subcellular localisation [108]. Sumoylated LRH-1 is localised to the transcriptionally inactive nuclear bodies, away from active chromatin.…”
Section: Post-transcriptional Regulation Of Lrh-1mentioning
confidence: 98%
“…Phosphorylation of the serine residues 238 and 243 located within the hinge region of LRH-1 via phorbol 12-myristate 13-acetate (PMA), was found to be important for LRH-1 transactivation [107]. Sumoylation of LRH-1 also occurs in the hinge region, allowing for additional control of its activity via regulation of its subcellular localisation [108]. Sumoylated LRH-1 is localised to the transcriptionally inactive nuclear bodies, away from active chromatin.…”
Section: Post-transcriptional Regulation Of Lrh-1mentioning
confidence: 98%
“…Furthermore, LRH-1 can replace Oct4 in the reversion of mouse somatic cells to pluripotent cells [45]. This reprogramming capacity of LRH-1 can be enhanced by mutations in SUMO-conjugated lysine residues, which prevents the localization of LRH-1 to transcriptionally inactive nuclear bodies and increases its transactivity [14]. The present study revealed the nuclear transport mechanism of LRH-1 and implied that mutation in residues essential for NLS function could inhibit the nuclear localization of LRH-1 and consequently may influence embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids pGFP-LRH1 and pMyc-LRH1 have been described previously [14]. After plasmid pGFP-LRH1 was digested with KpnI/BamHI or ClaI/BamHI, the ends were blunted with Klenow and then self-ligated to generate pGFP-LRH1 1-116 and pGFP-LRH1 .…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult mammals, NR5A2 is predominantly expressed in pre-adipocyte cells and in the liver, intestine, pancreas, ovary and testis (Falender et al, 2003;Liu et al, 2003), and is particularly highly expressed in ovaries (Zhao et al, 2007;Yang et al, 2009). Further study showed that NR5A2 is not expressed in the theca or in stromal cells, but is restricted to the granulosa and luteal cells (Fayad et al, 2004).…”
Section: Introductionmentioning
confidence: 99%